Analysis Using Open System Model on Logistics Department in Rumah Sakit Ibu dan Anak Kenari Graha Medika - Fauzi, Muhamad Ibnu; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2013)
The Logistics department in Rumah Sakit Ibu dan Anak Kenari Graha Medika (RSIA KGM) where this research is the department that act as the key of cost structure of firm that support the whole operation. The department focused on targets that stated as goals to be achieved that consist of stock, store supplies, administration, distribution to units, monitor and control, and response. Currently logistics department couldnâ€™t fulfill the target of their operation. The root cause of the research is the lack of standardized operational guidelines. The root cause is causing confusion in the department that resulting lost sales, defect supplies, and expired supplies. The method that used to reach the goals is open system model. The model acts as the guide to make a better system. The model which draws the input-throughput-output model with feedback looped to adapt throughput to the environment. The environment consist of all elements outside the system that have the potential to affect that all part of the system. The result will generate feedback that will be used for future transformation. The solution in this research will show the procedure of all logistics activities. Logistics activities in RSIA KGM consist of 6 main activities, they are order supplies, accept and check supplies, store supplies, grant request of supplies, return supplies, and documentation. The usage of stratified random sampling, colored tag, control card, Reorder point, and risk mitigation plan will become the way for logistics department to reach their targets. Even though the old system is simpler, but it is subjective and have disorganized activities. The proposed system have structured activities and standardized procedure, but in the other side the system is quite complex and it will need well trained employee.Â Keywords: Open system model, standard operational procedure, Reorder point,Â Logistic, Rumah Sakit Ibu dan Anak